FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME PENJUALAN EKSPOR PUPUK UREA PT PUPUK SRIWIDJAJA PALEMBANG - Sriati, Sriati; Misnasari, Leni; Lifianthi, Lifianthi (Fakultas Pertanian Universitas Mataram, 2025)
One of the industries that has a function to meet the needs of domestic agricultural inputs and has great market potential to reach the international market is the urea fertilizer industry. The purpose of this study is to analyze the factors that affect the sales performance of commercial urea fertilizer carried out through PT Pusri Palembang's export activities. This research was conducted at PT Pusri Palembang in November 2024. The research method used is a case study using secondary data on urea fertilizer exports in the 2009-2023 period. The result of this study is that the factor that has a significant influence on the export volume of PT Pusri Palembang is the production of urea fertilizer with a positive influence. Meanwhile, the factors of international urea prices, the exchange rate of the Rupiah against the USD, Indonesia's subsidized urea consumption, world urea production and potential countries' urea consumption have no significant effect.